Field Test of Clove Oil (Syzigium aromaticum) as Biolarvacide Against Mosquito Lavrae - Budiman Budiman; Sri Jumiyati; Hamidah Hamidah; Puput Puput; Rajindra Rajindra; Miswan Miswan (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: The vector control that should be carried out today is biological control made from natural ingredients to reduce the negative impacts of the use of chemicals. Therefore, this research aims to examine the ability of residual oil from clove leaves (Syzigium aromaticum) to kill the larvae of the mosquito through field tests. Methods: This research uses experimental methods carried out in the field. This investigation is a follow-up investigation based on laboratory test results. This research uses test larvae obtained directly from the field without going through the breeding process in the laboratory. This research used the concentration of clover leaf (Syzigium aromaticum) residual oil that was adopted from laboratory test results, that is, a concentration of 0.006%; 0.007%; 0.008%; 0.009% and 0.01%. This research uses guidelines from the WHO Guidelines testing standards. Results: The results of this research show that waste oil from clove leaves (Syzigium aromaticum) is capable of killing mosquito larvae in field tests. For Aedes aegyipti larvae, the concentration that is effective in killing larvae starts from a concentration of 0.008%-0.01%, while in tests with Culex sp and Anopheles sp larvae, leaf waste oil Clove (Syzigium aromaticum) is effective in killing larvae at all. concentrations (0.006-0.01%). The implications and significance of this research show that clove leaf (Syzigium aromaticum) waste oil has proven to be effective as a base for developing natural and economical larvicidal products and can support government programs to eradicate diseases such as dengue, malaria and chikungunya, which are caused by mosquito vectors Conclusion: Waste oil from clove leaves (Syzigium aromaticum) can be used as an alternative ingredient to kill Aedes aegypti, Culex sp and Anopheles sp mosquito larvae in field tests.